The passivity of adaptive output regulation of nonlinear exosystem with application of aircraft motions - Kumar, R. Ravi Ravi; Cao, Jinde; Alsaedi, Ahmad (Nonlinear Analysis: Modelling and Control, 2017)
This paper deals with passivity of adaptive output regulation of nonlinear exosystem. It is shown that factorisable low-high frequency gains and harmonic uncertainties are estimated to the exogenous signals with adaptive nonlinear system. The design methodology guarantees asymptotic regulation in the case where the dimension of the regulator is sufficiently large in relation, which affects the number of harmonics acting on the system. On the other hand, harmonics of uncertain amplitude, phase, and frequency are the major sources, and the bounded steady-state regulation error ensures that adaptive nonlinear system is globally asymptotically stable via passivity theory. Kalman–Yacubovitch–Popov property provides that the uncertain adaptive nonlinear system is passive. Finally, specific examples are shown in order to demonstrate the applicability of the result.
Keywords: Lyapunov function; output regulation; passivity